Impact of 24-hour Ambulatory Blood Pressure Monitoring on Early Neurological Outcomes in Acute Stroke: A Prospective Observational Study - Suryavir, Suryavir; Garg, Nischal; Saini, Tushar Krishnan (Journal of Neonatal Surgery, 2025)
Background and Objective:The role of blood pressure (BP) fluctuations during the acute phase of stroke remains controversial. This study aimed to assess the circadian pattern of BP using 24-hour ambulatory blood pressure monitoring (ABPM) in acute stroke patients and analyze its association with short-term neurological outcomes. Materials and Methods:A total of 108 patients with acute ischemic or hemorrhagic stroke, presenting within 24 hours of symptom onset, were enrolled. Initial BP readings were recorded using three supine measurements at 5-minute intervals, and the average was noted. ABPM was conducted on day 1, capturing various BP parameters over 24 hours. Functional status was assessed at admission using the Modified Rankin Scale (mRS), repeated on day 6 and at 1-month follow-up. BP patterns—dipper, nondipper, and reverse dipper—were identified and correlated with neurological recovery. Results:Most patients exhibited a nondipping BP pattern, followed by reverse dippers and dippers. Elevated mean 24-hour systolic BP (SBP), daytime SBP, and nighttime SBP were significantly associated with unfavorable functional outcomes (mRS 4–6) at both day 6 and 1 month. Higher initial and day 6 casual SBP and diastolic BP (DBP) were also predictive of worse prognosis at 1 month. Conclusion:In acute stroke patients, elevated 24-hour, daytime, and nighttime SBP values—especially in nondipping profiles—are strongly correlated with poor short-term neurological outcomes. ABPM may be a valuable tool in prognostication and early risk stratification in stroke care.